Assessing food security status of coconut farmers' households in Barangay Riverside, Calinan, District and Barangay Mulig, toril Davao City - Bolongaita, Rea Mae S.; Hualda, Luis Antonio T. (2016)
Food security is one of the emerging issues in the world today and one of the problems of households in rural areas, particularly, agricultural producers. Thus, there is a need for the assessment of the household food security. Moreover, assessment of the household food security at the household level is more effective since it gives a clearer picture of the situation. Household food security assessment of coconut farmers? households in Brgy. Riverside, Calinan and Brgy. Mulig, Toril Districts of Davao City is the focus of the study. Methodology of the study includes both qualitative and quantitative measures. A total of 90 coconut farmers' households were interviewed for the study. The Household Food Insecurity Access Scale was used in measuring the household food insecurity level. Quantile regression or median regression was the type of regression used in data analysis. The study found that most of the coconut farmers interviewed are severely food insecure. Also, the different coping strategies observed by the coconut farmers? households as well as the households' perception on meeting market demands and the households perception food accessibility have a significant impact on the household food security status of coconut farmers.
Thesis (BS Agribusiness Economics)-- University of the Philippines Mindanao, June 2016